The ethnography of police: Communication barriers in Mesuji conflict, Indonesia - Setiawan, Rudi; Mashud, Mustain; Sparingga, Daniel; Nurdin, Bartoven Vivit; Asnani, Asnani (ETNOSIA : Jurnal Etnografi Indonesia, 2023)
This research examines the experiences of police working in conflict areas, how they adapt to situations that are prone to conflict, including their views on the conflicting parties, namely the community, companies and local governments as well as the communication barriers they experience with the new culture. This research focuses on the stories of the duties of Bintara, namely the police with the lowest rank in the police structure in conflict areas in Mesuji Regency, Lampung Province, Indonesia. The stories of Bintara who served in this conflict area are very interesting to study and analyze after conducting long research on their lives. This study uses an ethnography approach with qualitative methods, where in-depth interviews and observation are data collection techniques. The results of this study indicate that there is no non-commissioned officer who wants to be placed in a tense area because of the conflict, threats to life that always loom, skin diseases, no clean water source, poisoned food, and communication barriers with the community are one cause, namely stereotypes and prejudices against conflict area communities. The stories of the police on duty as a result of this research are full of tension and life threats are explored in ethnography.